Pengaruh Model Pembelajaran Kooperatif Type STAD Terhadap Keterampilan Pengisian Partograf Mahasiswa Kebidanan - Yulizawati Yulizawati; Venny Rismawanti (SEAJOM: The Southeast Asia Journal of Midwifery, 2015)
Educational development demands different ways of thinking and act from what have already existed. Ideal learning system must be able to provide a learning experience for students, to open up their potential for internalizing knowledge, skills and attitudes through their learning experiences. It can be done by applying an active learning method through student centered learning (SCL), one of these methods is STAD (Student Teams Achievement Division). This type teaches cooperation, responsibility, interaction, confidence, decision-making, communication, and conflict management. With this method, partograph filling skill as the core competencies of midwifery students in labor monitoring may increase.. This research aims to determine the effect of STAD method on partograph filling skill of midwifery students. This was a comparative study to compare the level of student skill in filling up partograph before and after applying cooperative learning using STAD method. The results obtained in this study showed that there was a very significant difference of the skill of students before and after using cooperative learning of STAD method, with a p-value is 0.001. Student centered learning using STAD method is proved to be more significant to improve student competence of filling up partograph.